Pengaruh Media Pembelajaran Dapur (Roda Putar) terhadap Pemahaman Konsep Matematika pada Materi Perkalian - Nur Kholifah Alviana; Dewi Setiyaningsih (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to determine the effect of using the Rotating Wheel (DaPur) learning media on the understanding of multiplication concepts of second-grade students at Tugu Utara 03 Elementary School, North Jakarta. The study was conducted in February 2025 with a quantitative approach and quasi-experimental design. The research sample consisted of 60 students divided into two classes, namely class II A as the control group and class II B as the experimental group, each consisting of 30 students. Data collection was carried out through the administration of pre-tests and post-tests. The instruments used have been tested for validity and reliability, with the results that all questions were declared valid and reliable (Cronbach's Alpha = 0.896). Data were analyzed using an independent sample t-test. The results of the analysis showed that there was a significant difference between the post-test scores of students in the experimental class and the control class, with a t-value of 27.757 and a significance of 0.001 (<0.05). This proves that the rotating wheel media has a positive and significant effect on the understanding of multiplication concepts. The Spinning Wheel media has been proven to help students understand multiplication material in a more enjoyable and concrete way, thereby improving their abilities in the aspects of translation, interpretation, and extrapolation of concepts. Based on these results, it can be concluded that the Spinning Wheel (DaPur) media is effective for use in mathematics learning, especially multiplication material.